Association Between IL16 Gene Polymorphism and Allergic Contact Dermatitis Among Construction Workers. (October 2019) - Khashaba, Eman Omar; Gaballah, Mohammad A; State, Ahmed Fathy; Elwassefy, Mona
Objectives: First, this research was instituted to identify common allergens, and second, to test the association between IL16 gene promoter polymorphism rs4778889 T/C and allergic contact dermatitis (ACD). Methods: A case control study was conducted in dermatology outpatients' clinic. Study subjects received interview-based semi-structured questionnaire, complete skin examination, IL16 gene promoter was investigated by PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) analysis, and IQ Ultra™ patch test units (Chemotechnique Diagnostics AB, Sweden) with 10 substances were used. Results: Most of the prevalent cases had positive patch test (93.3%). The most common clinical presentation of ACD in our patients was itching (96.7%), followed by dryness (86.75%), erythema (76.7%), and fissuring (76.7%). There was higher CC gene distribution among cases, but there was no statistically significant difference. IL16 gene distribution was nearly similar among different clinical presentations. Formaldehyde showed statistically significant higher frequency for CC. The most common allergen found was mercury chloride (76.6%), followed by potassium dichromate (26.6%) and cobalt chloride (20%). Conclusions: The current study found prominent metal sensitization (mercury chloride) over the previously known potassium dichromate. There was no statistically significant IL16 gene distribution among cases compared with control. However, C allele was more frequently encountered in cases. Further studies are required to test the association with IL16 genotype and ACD and highlight the new trends in metal sensitization among cement-exposed workers.